PERAN BRAND IMAGE MEMEDIASI HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN PADA TIKTOK SHOP - Cahyani Nesanta, Ketut Egi; Sukawati, Tjokorda Gde Raka; Ekawati, Ni Wayan (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.12.TAHUN.2023DO - 10.24843/EEB.2023.v12.i12.p07, 2023)
This study aims to examine and explain the role of brand image in mediating the effect of price and service quality on purchasing decisions at the TikTok Shop. This research was conducted in Denpasar City with a total sample taken of 126 respondents with the method of determining the sample, namely purposive sampling. The data analysis technique used is path analysis, Sobel test and VAF test. The results showed that price had a positive and significant effect on purchasing decisions, service quality had a positive and significant effect on purchasing decisions, price had a positive and significant effect on brand image, service quality had a positive and significant effect on brand image, brand image had a positive and significant effect on decisions purchase, brand image is positively and significantly able to mediate the effect of price on purchasing decisions, and brand image is positively and significantly able to mediate the effect of service quality on purchasing decisions. This research is expected to provide an empirical contribution to management science, especially consumer behavior and be useful for TikTok Shop companies in developing product marketing strategies related to the company's brand image, price, and service quality.